Holistic Healing: Panchakarma Therapy for Spino-Cerebellar Ataxia Management - Sowjanya B R; Ananta. S. Desai (AYUSHDHARA, 2025)
Spino-Cerebellar Ataxia (SCA) is a genetic disorder that gradually affects movement, balance, and speech. It occurs due to the weakening of the brain's coordination center (cerebellum) and the spinal cord. This leads to symptoms like difficulty walking, shaky hand movements, slurred speech, and trouble swallowing. In Ayurveda, it is linked to Dhathu-Kshayajanya Vatavikara, which refers to conditions caused by tissue degeneration and imbalance in body energy. A 24-year-old man visited the hospital with complaints of walking, writing, and speaking difficulties for five years, which had worsened in the last two years. He underwent a 14-day Panchakarma therapy, including Abhyanga, Parisheka, Shastika shali pinda sweda and Madhutailika Basti. These treatments significantly improved his ability to walk and control hand movements. Ayurveda takes a holistic approach to managing SCA by addressing both the symptoms and their root cause. These therapies not only provide relief but also support long-term well-being, making them a promising treatment option for this condition.